Antibacterial Effects of Grape Extracts on Helicobacter pylori - Brown, Joseph C; Huang, Guohui; Haley-Zitlin, Vivian; Jiang, Xiuping (Applied and Environmental Microbiology, 2009)
Anti-Helicobacter pylori activities were determined by agar dilution, confocal laser scanning microscopy, and cell proliferation assays following treatment with various grape extracts. Muscadine grape skin possessed the strongest activity, followed by grape synergy (skin and seed) and seed, suggesting that higher phenolic levels do not necessarily determine overall anti-H. pylori efficacy.